INFLUENCE OF BREEDING TECHNOLOGY ELEMENTS ON THE FORMATION SEEDING TARTAR BUCKWHEAT IN THE WESTERN FORESTSTEPPE CONDITIONS - Харевський, Є. В.; Гаврилянчик, Р. Ю. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The article presents the results of research to study the characteristics of the formation of crops Tartar buckwheat under the influence of pre-sowing seed treatment, in particular on the vigor and germination and foliar fertilizers and fertilizer application phase of plant density and their survival under laboratory and field conditions. It was established that in the conditions of the southern part of the western forest-steppe, the tartar buckwheat grains were the most affected by the processing of seeds by the fertilizer Wuxal Terios, and by the vegetative use of fertilizers Wuxal Bio Ascofol and Wuxal Bio Aminoplant. The results of the research confirm that the use of Wuxal Terios increases the field similarity of tartar buckwheat seed by 5.8%. The plant density and their survival depended on the characteristics of extra-root fertilization in a certain phase of growth and development. The largest number of plants before harvesting was when using Wuxal Bio Ascofol in the full flowering phase of 174.7 pcs./m2, with the processing of seed material, with survival of 97.2%. When Waxal Bio Aminoplant is introduced into the budding phase without seed treatment, the largest plant density at the end of the vegetation is 159.6 pcs./m2, and the plant survival is 94.5%. It is proved that the use of Wuxal fertilizer increases seed germination, significantly changes the biometric parameters and increases the yield of crops of Tartar buckwheat